2010
DOI: 10.1038/ejhg.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

Cervix smear abnormalities: linking pathology data in female twins, their mothers and sisters

Abstract: Mass screening for cervical cancer precursors has decreased the incidence of cervical cancer in several countries, including the Netherlands. Persistent infections of certain types of human papillomavirus are strongly associated with the development of cervical cancer. A number of factors may affect the liability to infection and subsequent progression to cervical intraepithelial neoplasia and cancer. This paper examines whether genetic factors are involved in explaining individual differences in liability. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Of these, 12 appeared to have utilized a classical twin design and examined the risk of cervical cancer and its precursor lesions, and thus were selected to undergo a full-text review. After a full-text review, 9 of the 12 articles were excluded; two did not include twin pairs (Magnussen, Lichtenstein, & Gyllensten, et al, 1999;Magnussen, Sparen, & Gyllensten, 2000), five did not utilize a classical twin design but evaluated twinning itself as a risk factor (Braun, Ahlbom, Floderus, Brinton, & Hoover 1995;Hemminki & Li, 2002;Iversen, Tretli, & Kringlen, 2001;Neale, Mineau, Whiteman, Brownbill, & Murphy, 2005;Neale et al, 2004), one reported results aggregated for all cancers, not specifically cervical cancer (Verkasalo, Kaprio, Koskenvuo, & Pukkala, 1999), and one did not report data on dizygotic pairs separately from other first-degree relatives (Vink et al, 2011). Therefore, three articles met our inclusion criteria (Ahlbom et al, 1997;Lichtenstein et al, 2000;Thomsen, Jochumsen, & Mogensen, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 12 appeared to have utilized a classical twin design and examined the risk of cervical cancer and its precursor lesions, and thus were selected to undergo a full-text review. After a full-text review, 9 of the 12 articles were excluded; two did not include twin pairs (Magnussen, Lichtenstein, & Gyllensten, et al, 1999;Magnussen, Sparen, & Gyllensten, 2000), five did not utilize a classical twin design but evaluated twinning itself as a risk factor (Braun, Ahlbom, Floderus, Brinton, & Hoover 1995;Hemminki & Li, 2002;Iversen, Tretli, & Kringlen, 2001;Neale, Mineau, Whiteman, Brownbill, & Murphy, 2005;Neale et al, 2004), one reported results aggregated for all cancers, not specifically cervical cancer (Verkasalo, Kaprio, Koskenvuo, & Pukkala, 1999), and one did not report data on dizygotic pairs separately from other first-degree relatives (Vink et al, 2011). Therefore, three articles met our inclusion criteria (Ahlbom et al, 1997;Lichtenstein et al, 2000;Thomsen, Jochumsen, & Mogensen, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the risk of developing cervical cancer was found to be approximately twofold higher among biological first-degree relatives of cervical cancer patients, compared to their nonbiological relatives [48]. Furthermore, a recent large-scale study showed that monozygotic twins shared significantly more similar results in cervical smear test compared to dizygotic twins and other first-degree relatives [49]. Based on these epidemiological studies, the genetic heritability of cervical smear abnormality and invasive cervical cancer has been determined as 37 and 27 %, respectively [49,50].…”
Section: Emerging Player In Cervical Cancer Susceptibility: Genetic Fmentioning
confidence: 93%
“…Furthermore, a recent large-scale study showed that monozygotic twins shared significantly more similar results in cervical smear test compared to dizygotic twins and other first-degree relatives [49]. Based on these epidemiological studies, the genetic heritability of cervical smear abnormality and invasive cervical cancer has been determined as 37 and 27 %, respectively [49,50]. The genetic heritability of cervical cancer is therefore higher than that for colorectal and lung cancers.…”
Section: Emerging Player In Cervical Cancer Susceptibility: Genetic Fmentioning
confidence: 97%
“…Information on chorionicity through record linkage as well as access to tissue samples was available from in the Pathological Anatomy National Automatic Archive (PALGA), a nationwide network and register of histopathology and cytopathology database and biobank. Other projects that made use of the PALGA database include studies on triplets and a study of cervix smear abnormalities (Lamb et al, 2012;van Beijsterveldt et al, 2016;Vink et al, 2011). Valuable information can also be obtained by linking the NTR databases to national population-based registers such as the cancer registration in the Netherlands.…”
Section: Record Linkage/cross-referencing the Ntr Database To Other Nmentioning
confidence: 99%